2016
DOI: 10.1186/s12917-016-0883-5
|View full text |Cite
|
Sign up to set email alerts
|

Change in the responsiveness of interferon-stimulated genes during early pregnancy in cows with Borna virus-1 infection

Abstract: BackgroundBorna disease virus is a neurotropic pathogen and infects the central nervous system. This virus infected a variety of animal species including cows. The most of cows infected with Borna disease virus 1 (BoDV-1) exhibit subclinical infection without any neurological symptoms throughout their lifetime. We previously reported on the low conception rates in-seropositive cows. Interferon-τ (IFN-τ) plays an important role in stable fertilization, and is produced from the fetal side following embryo growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
(28 reference statements)
2
5
0
Order By: Relevance
“…This interaction was explained by greater ISG15 ratio in diseased pregnant cows compared with healthy pregnant cows but lesser ISG15 ratio in diseased nonpregnant cows compared with healthy nonpregnant cows. Takino et al (2016) reported results similar to ours where Borna virus 1-infected (seropositive) pregnant cows had greater ISG15 expression compared with seronegative pregnant cows (Takino et al, 2016). Takino et al (2016) also observed lower P/AI in the infected cows.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This interaction was explained by greater ISG15 ratio in diseased pregnant cows compared with healthy pregnant cows but lesser ISG15 ratio in diseased nonpregnant cows compared with healthy nonpregnant cows. Takino et al (2016) reported results similar to ours where Borna virus 1-infected (seropositive) pregnant cows had greater ISG15 expression compared with seronegative pregnant cows (Takino et al, 2016). Takino et al (2016) also observed lower P/AI in the infected cows.…”
Section: Discussionsupporting
confidence: 80%
“…Takino et al (2016) reported results similar to ours where Borna virus 1-infected (seropositive) pregnant cows had greater ISG15 expression compared with seronegative pregnant cows (Takino et al, 2016). Takino et al (2016) also observed lower P/AI in the infected cows. Their conclusion was that diseased cows may require greater INFT signaling (and hence greater ISG15) for the establishment of pregnancy.…”
Section: Discussionsupporting
confidence: 80%
“…As pDC of other species have repeatedly been described for their ability to rapidly produce large amounts of type I interferons [6], the cytokines that are essential for innate immune responses against viruses [87], we were surprised to find that bovine pDC only marginally upregulated IFN gene expression upon TLR stimulation. Most of the studies that have investigated bovine IFN responses have either detected mRNA for bovine type I IFN [88,89] or mRNA for ISGs [90,91] by quantitative RT‐PCR with total RNA samples from blood or tissues, or have looked at IFN activity by Mx‐CAT reporter assays [92‐96]. Two studies [92, 96] found type I IFN activity in cells that phenotypically resemble the current phenotypic definition of bovine pDC [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several signalling pathways (e.g. p38 MAPK and class III phosphatidylinositol-3 kinase (PI3K/Akt) may induce or inhibit apoptosis (Assefa et al, 2000;Tsuruta et al, 2002), and the activation of these pathways has been previously investigated in BVDV-infected cells (Bendfeldt et al, 2007). Akt is a well-characterized anti-apoptotic signal that promotes survival in many cell types; accordingly, we assessed the phosphorylation of Akt by immunoblotting.…”
Section: Autophagy Induction Reduces Apoptosismentioning
confidence: 99%